TECHNOLOGY AND ECONOMY FOR OBTAINING COAL THERMAL PLASTICIZER – WATER PROOFING COMPONENT IN STRUCTURES OF MAN-MADE OBJECTS - G. D. Liakhevich; A. G. Liakhevich (Наука и техника)
The paper describes development of the technology for obtaining thermal plasticizer from the Kansk-Achinsk brown coal while using a method of thermal destruction  in а hydrocarbon medium: oil selective purification extract or used motor oil mixtures. Coal thermal plasticizers have been used for production of unsupported roll-fed water proofing materials. The paper shows an economic effect of which can be ensured while obtaining a thermal plasticizer from brown coal.